A case of acute compartment syndrome of upper limb in a dengue haemorrhagic fever patient secondary to intravenous cannula insertion - Subramaniam, Kishan Rao; Karupiah, Rajandra Kumar; Raj, Jeffry; Zakaria@Mohamad, Zamzuri (Crimson Publishers, 2019)
Dengue fever with its haemorrhagic complications is a common viral illness in Malaysia which can sometimes lead to high morbidity and mortality. We present a case report of a 27-year-old male who was admitted to our hospital with dengue haemorrhagic fever. He developed multiple hematomas and bruising in his right forearm and arm due to intravenous cannula insertion. Due to coexisting thrombocytopenia, the limb progressed to acute compartment syndrome and emergency fasciotomy was done and his limb was salvaged. This case illustrates an important potential complication of dengue fever and the importance of timing of surgery in the event of compartment syndrome.